Letter (copy) : International Solidarity Fund - Tewson, Vincent
034-0184-001 HVT/EK/596. Secretary's. 25th March, 1937. Mr. A. Taylor, The Rossendale Union of Boot, Shoe and Slipper Operatives, 7, Tenterfield Street, Waterfoot Rossendale. Dear Mr. Taylor, INTERNATIONAL SOLIDARITY FUND. Referring to your letter of the 23rd instant, the National Council of Labour has considered the question as to whether the monies of the International Solidarity Fund raised for the assistance of workers in Spain should be used to assist dependents of the British Section of the International Brigade in Spain. It has been ascertained that in many cases local arrangements are being made far assistance by Trade Union branches, etc. in respect of their members and this fact, together with the shortage of funds, the purpose for which the money was subscribed, and the unlimited time for which demands might be made has led them to the opinion that the Fund should not be used for the purpose mentioned. Yours sincerely, Assistant Secretary. 292/946/34/184